STUDYING OF EARLY CHILDHOOD EDUCATION DEVELOPMENT IN THE TIMES OF UNR BY MEANS OF ELECTRONIC PRESENTATION - Artemova, L.V. (Journal of Information Technologies in Education (ITE), 2015)
Development of the students’ competences which consist of the three main groups (general,instrumental, interpersonal) provides education of high quality. The instrumental one means “computer skills and information management abilities”. That is the reason why pedagogical staff and students have to master information technologies on the appropriate level. Structural and methodological peculiarities of e-presentations usage on “Early Childhood Education Development in the Times of UNR” topic at lectures, seminars and students’ individual work are considered in the article. The represented methodology of e-presentations usage supplies interactive educational activities of students and teachers. It is considered as a complex of different tasks. It promotes cognitive activities, encourages interest for mastering the content, directs students to use active methods of teaching.